Reading Women in Late Medieval Europe - Thomas, Alfred. author. aut Link
XVII, 251 p.
Keywords: Although Chaucer is typically labeled as the "Father of English Literature," evidence shows that his work appealed to Europe and specifically European women. Rereading the Canterbury Tales , Thomas argues that Chaucer imagined Anne of Bohemia, wife of famed Richard II, as an ideal reader, an aspect that came to greatly affect his writing.